Lexical patterns in the reading comprehension section of the toefl test - Macmillan, Fabiana (Revista do GEL, 2006)
The TOEFL (Test of English as a Foreign Language) is currently one of the most widely accepted English language proficiency tests. Designed by the ETS (Educational Testing Service), the main purpose of the TOEFL is to determine whether the English language skills of a student applying to a North American college or university are adequate for enrollment into the selected program of study. This study will focus upon the third section of the TOEFL, Reading Comprehension, which consists of several passages followed by questions with different testing purposes. An adaptation of Hoey’s (1991) analytical system for the analysis of lexical cohesion in authentic texts will be used to identify bonds connecting reading comprehension questions on the test to key excerpts in the passages they are related to. A number of sample reading comprehension questions taken from practice tests produced by the ETS will be analyzed. The analysis will focus on the relationship between the testing purpose of each question and the type(s) of lexical link involved in the identification of the correct answer.